Personal Branding of Female Virtual Biography Users on the Bumble Dating Application in a Romantic Relationship - Lestari, Anggita; Salma, Siti; Hanaf, Hanafi; Reza, Faisal (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Bumble is a dating platform that empowers women during the initiation phase of romantic relationships. With the "women make the first move" feature, the application creates a more controlled and secure experience for women in the realm of online dating. In this app, personal branding serves as a method to shape an individual's image in the eyes of others, reflecting the portrayal of women through virtual biographies. This research focuses on female users of dating apps in Indonesia, aiming to understand the personal branding strategies employed by women. The research method involves a qualitative approach with a case study methodology. Data collection techniques include observation, interviews, and documentation, while informant selection utilizes purposive sampling. The study's findings reveal that the personal branding strategies of female dating app users in Indonesia encompass competency aspects such as interests or hobbies in sports, makeup, and writing. Individual styles, both in communication without small talk and in clothing that reflects either a glamorous or simple style. Standards for seeking a partner involve shared preferences in humor or the partner's level of activity in interactions. Thus, personal branding in dating apps serves as a means to construct the virtual biography and image of women.